Evaluating the Flipped Classroom for Enhancing Student Collaboration: A Systematic Literature Review - Mhd Arya Dhaifullah; Resmi Darni; Yeka Hendriyani; M Giatman (STAI Hubbulwathan Duri, 2026)
The flipped classroom (FC) model has gained prominence in higher education, yet its effectiveness in fostering student collaboration remains inconclusive. This study systematically reviews existing literature to examine how FC implementation influences collaborative learning outcomes. A systematic literature review was conducted following the PRISMA framework. Ten empirical studies published between 2015 and 2023 were selected based on predefined inclusion criteria. The studies were analyzed with a focus on instructional design, assessment alignment, and the operationalization of collaboration. The findings reveal that while FC approaches are widely adopted, their impact on collaboration varies considerably. Studies that explicitly structured collaborative roles and aligned collaboration with assessment practices reported stronger outcomes. In contrast, studies that treated collaboration implicitly or descriptively demonstrated weaker or inconsistent results. Additionally, collaboration was often insufficiently defined or measured as a primary learning outcome. The review identifies significant gaps in the literature, including limited conceptualization and measurement of collaboration, as well as a lack of longitudinal and discipline-specific research, particularly in Informatics Engineering. These findings suggest that FC environments do not inherently enhance collaboration. More rigorous research designs that explicitly integrate and assess collaboration are needed to better understand and optimize its role within flipped learning contexts.